Balancing Growth and Sports: The Impact of Sever’s Disease on Young Athletes - Adamiec, Ksawery; Nowak, Dominika; Graczyk, Szymon; Trojanowski, Dominik; Tłoczek, Wiktoria; Zdziebko, Aleksandra; Dziuk, Kamil; Azierski, Michał; Twardowska, Daria; Gadocha, Piotr (Quality in Sport, 2024)
This article provides a comprehensive analysis of calcaneal apophysitis, or Sever’s disease, a major cause of heel pain in children. This overuse injury stems from repetitive mechanical stress on the calcaneal apophysis, often intensified by rapid growth spurts and high physical activity. It is particularly prevalent among young athletes involved in sports with repetitive impact. The condition’s pathophysiology involves microtrauma and inflammation at the calcaneus’s secondary ossification center due to traction forces from the Achilles tendon. Diagnosis is primarily clinical while imaging is used to rule out other conditions. Symptoms include localized heel pain and tenderness, worsened by activity. Risk factors encompass intrinsic elements like limited ankle dorsiflexion and foot alignment issues, and extrinsic factors such as intense physical activity. Management mainly involves conservative treatments: rest, NSAIDs, stretching exercises, and orthotics. Physical therapy and proper footwear are also effective. Prevention focuses on maintaining a healthy weight, adequate rest, supportive footwear, low-impact activities, and regular stretching to reduce re-injury risk.